Vegetative and reproductive responses, oil yield and composition from olive trees (Olea europaea) under contrasting water availability during the dry winter-spring period in central Argentina - Pierantozzi, Pierluigi (2014)
In Argentina, the climatic pattern of the olive production areas is characterised by a marked water deficit during winter and spring months. A field experiment was carried out to evaluate the effect of water availability during the preflowering? flowering period on vegetative, reproductive and yield responses of olive trees grown in central Argentina. From the end of autumn to mid-spring, four irrigation treatments were imposed to olive trees (Olea europaea, cv. Arbequina and Manzanilla) at 0, 25, 50 and 75% estimated crop evapotranspiration (ETc). Also, a control treatment was kept at 100% ETc for the entire year. For the first crop year evaluated, water deficit applied at early June, approximately 4 months prior to bloom, reduced the vegetative shoot growth and delayed the flowering time, resulting in shortening of the fruit maturation period and, ultimately, decreased fructification. Trees irrigated with high (75% of ETc) and full (100% of ETc) winter-spring water supply presented significantly higher values of flower density, fruit density and final fruit yield which resulted in water productivity (kg fruitsmm−1 of irrigation/ha) enhancements of about 500% (cv. Arbequina) and 330% (cv. Manzanilla) with respect to those obtained from the corresponding unirrigated treatments. Differences between treatments in oil content and composition were primarily attributed to variations in fruit maturity. Differences in fatty acid composition were stronger in cv. Arbequina where a gradual increase in oleic acid content was registered in parallel to the increase in irrigation water supply. From a practical stand point, results obtained from most of the analysed parameters were quite similar for both T75 and T100 treatments. Thus, the possible convenience of irrigation at T75% ETc should be considered since it may warrant profitable olive production while saving a considerably quantity of irrigation water in the olive production area in central Argentina.